(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the relationship of functionyms that relate to the mediostructure of the dictionary and the phenomena of the lexical-thematic group and the lexical-semantic field, which were the main types of the macrostructure of the vocabulary.